Social and Individual Processes at the Time of the COVID-19 Crisis - Giuseppe Maiello (Culture e Studi del Sociale)
The author presents eight studies carried out during the global pandemic of coronavirus disease 2019 (COVID-19) and focuses on different methodological issues to be addressed within the Digital Society and netnographic research. The studies are reported in a common context ranging from the individual experiences of researchers to the receipt of political propaganda in mass society through social media.